Предмет: Алгебра, автор: szhandarmova

√2*cosx-1=0 ,
3tg 2x+√3=0

Ответы

Автор ответа: o1l7eg17
0
Первое уравнение крайне легкое.
 sqrt{2}cosx-1=0
 sqrt{2}cosx=1
cosx= frac{1}{ sqrt{2} }
x=± arccos frac{1}{ sqrt{2} }+2 pi n ; n∈Z
x=± frac{ pi }{4}+2 pi n ; n∈Z
2) 3tg(2x)+ sqrt{3}=0
3tg(2x)=- sqrt{3}
tg(2x)=- 3^{ frac{1}{2}- 1}
tg2x=- frac{1}{ sqrt{3} }
2x=  pi n-arctg( frac{1}{ sqrt{3} }) ; n∈Z
x= frac{ pi n}{2}-  frac{ pi }{12} ; n∈Z
Похожие вопросы
Предмет: Английский язык, автор: portiankozena5